Comparison study of ferrofluid and powder iron oxide nanoparticle permeability across the blood–brain barrier - Hoff D; Sheikh L; Bhattacharya S; Nayar S; Webster TJ (International Journal of Nanomedicine, 2013)
Dan Hoff,1 Lubna Sheikh,2 Soumya Bhattacharya,2 Suprabha Nayar,2 Thomas J Webster11School of Engineering, Brown University, Providence, RI, USA; 2Biomaterials Group, Materials Science and Technology Division, CSIR-National Metallurgical Laboratory, Burmamines, Jamshedpur, IndiaAbstract: In the present study, the permeability of 11 different iron oxide nanoparticle (IONP) samples (eight fluids and three powders) was determined using an in vitro blood–brain barrier model. Importantly, the results showed that the ferrofluid formulations were statistically more permeable than the IONP powder formulations at the blood–brain barrier, suggesting a role for the presently studied in situ synthesized ferrofluid formulations using poly(vinyl) alcohol, bovine serum albumin, collagen, glutamic acid, graphene, and their combinations as materials which can cross the blood–brain barrier to deliver drugs or have other neurological therapeutic efficacy. Conversely, the results showed the least permeability across the blood–brain barrier for the IONP with collagen formulation, suggesting a role as a magnetic resonance imaging contrast agent but limiting IONP passage across the blood–brain barrier. Further analysis of the data yielded several trends of note, with little correlation between permeability and fluid zeta potential, but a larger correlation between permeability and fluid particle size (with the smaller particle sizes having larger permeability). Such results lay the foundation for simple modification of iron oxide nanoparticle formulations to either promote or inhibit passage across the blood–brain barrier, and deserve further investigation for a wide range of applications.Keywords: ferrofluids, iron oxide nanoparticles, permeability, blood–brain barrier